Contribuição ao estudo do desempenho de biorreatores airlift de circulação interna: análise das condições operacionais e da geometria do equipamento - Esperança, Mateus Nordi (2018)
The high oxygen transfer capacity associated with low energy consumption have made the airlift bioreactor an important equipment to be used in bioprocesses, with the performance of these devices being strongly dependent on their geometry. In order to extend the understanding of the relationship between hydrodynamics and mass transfer of these equipment and their construction project, the objective of this thesis was to evaluate the effect of the geometry on the performance of 10 L internal-loop airlift bioreactors of different models (concentric duct and split) and with different cross-sectional shapes (circular and square). By evaluating the volumetric oxygen transfer coefficient (kLa) and the global gas hold-up (εG), a strong influence of the gas-liquid separator geometry was observed, while a small effect of the bottom geometry was verified. On the other hand, the liquid circulation velocity was affected by the geometry of all regions of airlift bioreactors (riser, downcomer, bottom, gas-liquid separator), exhibiting a high effect of the downcomer-to-riser cross-sectional ratio (AD/AR). Four promising geometries of square cross-section airlift bioreactors were selected based on oxygen transfer coefficient (kLa) and riser superficial liquid velocity (ULR) criteria, exhibiting different kLa and ULR levels for the same specific air flow rate (3 vvm), demonstrating the flexibility of airlift bioreactors to attend specific bioprocess requirements. By establishing an analogy between the gas-liquid flow in a concentric duct airlift bioreactor and the liquid flow in a smooth pipe, it has been found that computational fluid dynamics (CFD) can be satisfactorily applied to predict the shear rate. A non-uniform distribution of this parameter was observed in airlift bioreactors, where the maximum shear rate was observed close the sparger holes, showing a direct relationship with the gas injection velocity. In this way, the design of the gas sparger was the key parameter to the definition of maximum shear conditions in pneumatic bioreactors and should be considered in the project of these equipments.